Retrospective Evaluation of Potassium Hydroxide Mounts and Fungal Cultures in Suspected Mycotic Keratitis at a Tertiary Eye Care Center in South India - Swetha Mallagundla; Samyakta Shetti; Vidhya S Eswaran; Shraddha Sudarshan; Umme Kulsum; Swetha Shubraj; Mohsina Mekhri (RGUHS National Journal of Public Health)
Aim To evaluate the diagnostic utility of Potassium Hydroxide KOH wet mounts and fungal cultures FC in clinically suspected mycotic keratitis cases.Methods A retrospective study was conducted analyzing microbiological records of 150 patients with suspected mycotic keratitis from November 2016 to November 2017 at a tertiary eye care center in South India. Fungal cultures were performed on Sabouraud Dextrose Agar for at least three weeks. KOH wet mounts were conducted on 87 samples while 63 were untested due to drying 37 or insufficient sample volume 26. Demographic data KOH results fungal cultures and species isolated were analyzed using SPSS software version 2.0 applying the Pearson Chi-Square test P lt0.05 considered significant.Results Patients ranged in age from 2 to 89 years with a higher prevalence of males n90 compared to females n60. KOH wet mounts were positive in 24 27.6 and negative in 63 72.4 samples. Fungal cultures were positive in 84 cases 56 and negative in 66 44. Among the 24 KOH-positive samples 17 also had positive fungal cultures while 7 showed no fungal growth. Fusarium was the most commonly isolated species followed by Aspergillus.Conclusion The KOH wet mount serves as a rapid diagnostic tool for detecting fungal hyphae in mycotic keratitis with a greater likelihood of fungal isolation in KOH-positive cases. However a negative KOH result does not rule out fungal culture positivity. High clinical suspicion is crucial in treating corneal ulcers given the burden of fungal infections as a leading cause of mycotic keratitis in developing countries.